European Citizenship, Identity and Rights: A Survey on Italian Young Students - Guzzo, Tiziana; D’Andrea, Alessia; Ferri, Fernando; Grifoni, Patrizia (European Scientific Journal, ESJ, 2018)
Developing Europe means, first of all, creating a pervasive feeling of European citizenship, and creating a sense of belonging to a community in all countries of the European Union. This paper focuses on extracting Italian students’ socio-psychological dimension with respect to their perception and feelings regarding European citizenship, and their knowledge of the most relevant rights. The study involves Italian students aged between 18 and 25. A hybrid methodology has been adopted, combining: data extracted from a questionnaire; text from the photo-stories; images of the photo-stories and interviews. The results underline that young people have a sense of belonging to the European community, with the same rights and benefits. Moreover, there is the need to have the same feeling of European citizenship everywhere in Europe. The request for a stronger and more active citizens’ involvement also emerged from the study.